The Perineal Turnover Perforator Flap: A New and Simple Technique for Perineal Reconstruction After Extralevator Abdominoperineal Excision. Issue 4 (April 2018) - Chasapi, Maria; Maher, Mohamed; Mitchell, Peter; Dalal, Milind
Abstract : Background: Extralevator abdominoperineal excision (ELAPE) is increasingly used to treat locally advanced low rectal cancer as it has been related to superior oncological outcomes than traditional abdominoperineal excision. However, ELAPE also has been associated with high perineal wound morbidity rates as it creates a larger perineal cavity than standard abdominoperineal excision. This greater defect, along with the effects of preoperative chemoradiation on wound healing, makes uneventful perineal reconstruction post-ELAPE a real challenge for the plastic surgeon. In this paper, the authors present a new technique for perineal reconstruction post-ELAPE, using a perforator, islanded, turnover, de-epithelialized local flap (perineal turnover perforator [PTO] flap). Methods: The PTO flap is raised based on perforators from internal pudendal artery. The flap is based on the concept that thick gluteal dermis can act as an "autologous dermal vascularized" substitute for the excised pelvic floor muscles, whereas the bulk of its subcutaneous tissue is used to obliterate dead space. Fourteen patients underwent perineal reconstruction using this approach. Patients' demographics, neoadjuvant chemoradiotherapy, histopathology, duration of surgery, follow-up, and complications were analysed retrospectively. Results: Median operating time was 49 minutes. There were no flap, donor site, or major wound complications. One patient had superficial skin dehiscence, and one patient developed perineal hernia. None of the patients developed chronic perineal pain. Conclusions: The PTO flap is a quick, simple yet safe and reliable option for perineal reconstruction after ELAPE that offers many advantages over the heretofore used reconstructive techniques including primary closure, myocutaneous flaps, and biological meshes.